SISTEM KERUANGAN WILAYAH DAN PERUBAHAN TINGKAT KEMISKINAN DI MASA PANDEMI COVID-19 - Isma Candra Jati Kusuma (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
The Covid-19 pandemic has caused major shocks, especially to the non-agricultural sector, triggering an increase in poverty in various regions. An area is composed of urban and rural areas with different characteristics of socio-economic activities. This study aims to analyze the relationship between the regional spatial system and changes in poverty during the Covid-19 pandemic. The research method used is quantitative analysis with descriptive statistics and spatial analysis. Based on the results of the study, it was found that the regional development in Sragen Regency tends to be faster in the area south of the Bengawan Solo River, the overall increase in poverty occurs in the Decile 4 category of society, and there is a link between the rural-urban geographic location and the pattern of changes in poverty. This research is expected to provide knowledge development related to the classification of regional hierarchies, assessment of the distribution of poverty and the factors that influence poverty vulnerability due to economic shocks.